2021
DOI: 10.1111/andr.13127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the icariin on endothelial microparticles, endothelial progenitor cells, platelets, and erectile function in spontaneously hypertensive rats

Abstract: Objectives:To investigate the effect of icariin on endothelial microparticles, endothelial progenitor cells, platelets, and erectile function in spontaneously hypertensive rats. Materials and methods:Twelve 8-week-old healthy male Wistar-Kyoto rats and 12 spontaneously hypertensive rats were randomly divided into four following groups:Wistar-Kyoto control group (normal saline 1 ml/d given by gavage), Wistar-Kyoto + icariin group (icariin 10 mg/kg × d dissolved in 1 ml normal saline and given by gavage), sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In ancient China, EF was commonly used to treat sexual dysfunction [3]. Icariin can enhance erectile function in spontaneously hypertensive rats by reducing endothelial microparticle levels in the blood and inhibiting platelet activation [22]. In male mice, icariin can improve sexual function through the PI3K/AKT/eNOS/NO signaling pathway [23].…”
Section: Icariin and Its Pharmaceutical Effectsmentioning
confidence: 99%
“…In ancient China, EF was commonly used to treat sexual dysfunction [3]. Icariin can enhance erectile function in spontaneously hypertensive rats by reducing endothelial microparticle levels in the blood and inhibiting platelet activation [22]. In male mice, icariin can improve sexual function through the PI3K/AKT/eNOS/NO signaling pathway [23].…”
Section: Icariin and Its Pharmaceutical Effectsmentioning
confidence: 99%
“…In the past few years, many studies have investigated and proved the role of icariin and icariside II in the treatment of erectile dysfunction [ 34 ]. An improvement in erectile function was observed in spontaneously hypertensive rats, since icariin successfully decreased the content of endothelial microparticles in their blood, from 1.58% in the control group to 1.01% [ 35 ]. In vitro studies indicated that icariin could lead to increased testosterone secretion [ 36 ].…”
Section: Icariin and Its Derivatesmentioning
confidence: 99%
“…Stem cells can self-replicate and differentiate into multiple cell types, which are widely used in regenerative medicine research. Recently, many studies have shown that ICA and ICAII can regulate the biological behaviors of a variety of stem cells, including bone marrow mesenchymal stem cells (BMSCs), adipose-derived stem cells (ADSCs), neural stem cells (NSC), endothelial progenitor cells, human umbilical cord mesenchymal stem cells (53)(54)(55)(56). Previous studies have demonstrated that ICA could induce BMSC proliferation, differentiation, and ameliorate prednisolone-induced BMSC apoptosis in vitro and in vivo (57,58).…”
Section: Tissue Resident Stem Cells Activationmentioning
confidence: 99%